Social Media for Teaching and Learning within Higher Education Institution: A Bibliometric Analysis of the Literature (2008-2018) - Hashim, Kamarul Faizal; Rashid, Ammar; Atalla, Shadi (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Research on the topic of social media for teaching and learning in the higher education have received much attention from academia and practitioners. Social media technology was acknowledged not only as an important communication tool between faculty members and students but also shows great potential as the next social learning platform that better serves the teaching, learning and administration of a higher education institute. Its informal setting allows more flexibility for both students and faculty members to teach and learn anywhere and everywhere. Despite its important, little is known about how this research topic is evolving within the literature. Hence, using a bibliometric analysis technique this study examines the trends, topics, and challenges addressed by previous research for the past ten years (2008-2018). The paper ends by discussing future research directions related to this topic.